2020
DOI: 10.3892/ijo.2020.5096
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic‑derived ferrichrome inhibits the growth of refractory pancreatic cancer cells

Abstract: Pancreatic cancer is associated with a poor prognosis due to challenges in early detection, severe progression of the primary tumor, metastatic lesions, and resistance to antitumor agents. However, previous studies have indicated a relationship between the microbiome and pancreatic cancer outcomes. Our previous study demonstrated that ferrichrome derived from Lactobacillus casei, a probiotic bacteria, exhibited tumor-suppressive effects in colorectal and gastric cancer, and that the suppressive effects were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…A combination treatment with gemcitabine together with Lactobacillus paracasei improved the efficacy of chemotherapy, showing lower levels of aspartate-aminotransferase (AST) and alanine aminotransferase (ALT) [ 181 ]. In addition, the antitumor effect of probiotic-derived ferrichrome ( Lactobacillus casei ) has been observed in 5-FU-resistant pancreatic cancer cells, presumably through p53 upregulation and induction of apoptosis [ 182 ]. Iwama et al reported that the effect of ferrichrome on CRC cells was superior to that of 5-FU or cisplatin [ 183 ].…”
Section: Microbiota Modulation As An Emerging Tool Towards Improved Response To Anti-cancer Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination treatment with gemcitabine together with Lactobacillus paracasei improved the efficacy of chemotherapy, showing lower levels of aspartate-aminotransferase (AST) and alanine aminotransferase (ALT) [ 181 ]. In addition, the antitumor effect of probiotic-derived ferrichrome ( Lactobacillus casei ) has been observed in 5-FU-resistant pancreatic cancer cells, presumably through p53 upregulation and induction of apoptosis [ 182 ]. Iwama et al reported that the effect of ferrichrome on CRC cells was superior to that of 5-FU or cisplatin [ 183 ].…”
Section: Microbiota Modulation As An Emerging Tool Towards Improved Response To Anti-cancer Therapiesmentioning
confidence: 99%
“…Iwama et al reported that the effect of ferrichrome on CRC cells was superior to that of 5-FU or cisplatin [ 183 ]. These observations suggest that probiotics exhibit antitumor effects mediated by molecules such as ferrichrome and could therefore be used as antitumor drugs in the future [ 182 ].…”
Section: Microbiota Modulation As An Emerging Tool Towards Improved Response To Anti-cancer Therapiesmentioning
confidence: 99%
“…This study suggests that ferrichrome can activate the JNK signaling pathway triggering apoptosis ( Figure 4 ), and is more effective with reduced adverse effects than the clinical drugs cisplatin and 5-fluorouracil. Further studies have found that ferrichrome can also restrain proliferation and induce apoptosis in other cancers, such as gastric cancer [ 199 ], HCC [ 200 ] and pancreatic cancer [ 201 ]. Fecal microbiota transplantation (FMT) is the reconstruction of the gut microbiota by transplanting fecal material from healthy donors to sick patients.…”
Section: The Microbiome and Cancermentioning
confidence: 99%
“…In addition, some components derived from probiotics also seem to exhibit antitumor activity. The ferrichrome extracted from Lactobacillus paracasei can inhibit the proliferation of pancreatic cancer cells and restrain pancreatic cancer cells resistant to 5-fluorouracil in a mouse model, indicating that the antitumor activity of probiotics may come from the active ingredients in probiotics [162]. In addition, probiotics seem to have the ability to reduce adverse postoperative reactions.…”
Section: The Beneficial Effects Of Bacteria On Pancreatic Cancer Chemotherapymentioning
confidence: 99%